ULAMA, INSTITUSI PENDIDIKAN, DAN KEKUASAAN PADA MASA KLASIK ISLAM; SUATU TINJAUAN SEJARAH SOSIAL POLITIS - Siregar, Mahmudin (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2017)
scholars are the successors of the teachings of the prophet, in the time of the prophet Muhammad SAW the cleric was given the role to teach Muslims about the teachings of Islam